How Are We Doing with Open Education Practice Initiatives? Applying an Institutional Self-Assessment Tool in Five Higher Education Institutions - Tannis Morgan (Athabasca University Press, 2021)
This collaborative self-study examines how five higher education institutions in British Columbia (BC), Canada, have achieved momentum with openness and are implementing and sustaining their efforts. A goal of this research was to see whether an institutional self-assessment tool—adapted from blended learning and institutional transformation research—can help to assess how an institution has progressed with its open education initiatives. By adopting both an appreciative and a critical approach, the researchers at these five BC institutions compared the similarities and differences between their institutional approaches and the evolution of their initiatives. The paper includes discussion of how a self-assessment tool for institutional open education practices (OEP) can be applied to OEP initiatives at an institutional level and shares promising practices and insights that emerge from this research.